The Infosys Case: Is High Severance Pay to the Top Brass justified? - Aurora, Rajinder; Gupta, Silpy (Gyan Management Journal, 2017)
The case deals with the pay controversy that rocked Infosys. The controversy was raked up with the top brass getting hefty pay packet. This was very different than what Mr. Murthy thought about the pay paid to the top brass. He was of the view that there should be some parity between what the lowest paid employee earns and what the top honcho takes home. He has alluded to 'compassionate' capitalism, besides raising doubts about the corporate governance practices being followed by Infosys. The issue becomes severe in the context of Infosys, as it has been known as a company that always adhered to healthy & transparent Corporate Governance policies.
Keywords: Infosys; Severance Pay; Corporate Governance; Compassionate Capitalism